2015
DOI: 10.1002/jsfa.7527
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of new rhizobial isolates improve nutrient uptake and growth of bean (Phaseolus vulgaris) and arugula (Eruca sativa)

Abstract: These new rhizobia isolates are attractive PGP alternatives to chemical fertilizers. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Applied studies. The development of crops such as bean (de Souza et al, 2016), green gram (Kumar et al, 2015), rice (Bhattacharjee et al, 2012), groundnut (Arora et al, 2001), crambe (de Aquino et al, 2018), lettuce or carrot (Flores-Félix et al, 2013) have been tested with the inoculation of different Rhizobium spp. The inoculation has resulted in different positive outcomes, such as increase of shoot mass (Bhattacharjee et al, 2012;de Souza et al, 2016;Flores-Félix et al, 2013), nitrogen plant content (Baba et al, 2015;Bhattacharjee et al, 2012;Flores-Félix et al, 2013) and root development (de Aquino et al, 2018) or reduced effects of pathogenic agents (Arora et al, 2001;Siddiqui et al, 2007).…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…Applied studies. The development of crops such as bean (de Souza et al, 2016), green gram (Kumar et al, 2015), rice (Bhattacharjee et al, 2012), groundnut (Arora et al, 2001), crambe (de Aquino et al, 2018), lettuce or carrot (Flores-Félix et al, 2013) have been tested with the inoculation of different Rhizobium spp. The inoculation has resulted in different positive outcomes, such as increase of shoot mass (Bhattacharjee et al, 2012;de Souza et al, 2016;Flores-Félix et al, 2013), nitrogen plant content (Baba et al, 2015;Bhattacharjee et al, 2012;Flores-Félix et al, 2013) and root development (de Aquino et al, 2018) or reduced effects of pathogenic agents (Arora et al, 2001;Siddiqui et al, 2007).…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…This data were consistent with our previous findings indicating the ability of strain 139SI to fix N2. The researchers reported that PGPR enhanced plant growth and yield, as well as enriching nutrients in plants via increased mineral uptake and assimilation (Adesemoye et al, 2009;Souza et al, 2015;Berger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their efficiency can be increased with adequate selection processes and agronomical practices. Intensive selection programs of highly efficient rhizobial strains have been carried out in the last few years in Brazil, as one of the main dry bean-producing countries, in order to select elite inoculants [28],[29].…”
Section: Exploring the Natural Diversity Of Rhizobia Nodulating Commomentioning
confidence: 99%